Internal translation of Gja1 (Connexin43) to produce GJA1-20k: Implications for arrhythmia and ischemic-preconditioning - Whisenant, Claire C.; Shaw, Robin M. (Frontiers in Physiology, 2022)
Internal translation is a form of post-translation modification as it produces different proteins from one mRNA molecule by beginning translation at a methionine coding triplet downstream of the first methionine. Internal translation can eliminate domains of proteins that otherwise restrict movement or activity, thereby creating profound functional diversity. Connexin 43 (Cx43), encoded by the gene Gja1, is the main gap junction protein necessary for propagating action potentials between adjacent cardiomyocytes. Gja1 can be internally translated to produce a peptide 20 kD in length named GJA1-20k. This review focuses on the role of GJA1-20k in maintaining cardiac electrical rhythm as well as in ischemic preconditioning (IPC). Connexin43 is the only ion channel we are aware that has been reported to be subject to internal translation. We expect many other ion channels also undergo internal translation. The exploration of post-translational modification of ion channels, and in particular of internal translation, has the potential to greatly increase our understanding of both canonical and non-canonical ion channel biology.